CUP QUALITY, PHYSICAL AND CHEMICAL PROPERTIES OF ROBUSTA COFFEE BEAN PRODUCED BY WET PROCESS METHODS - Yhulia Praptiningsih S (UNEJ e-Proceeding, 2012)
The quality of smallholder coffee could be improved by wet process method. Natural fermentation method (removing mucilage by fermentation) produced good qualityof coffee bean, but it need long time process (24-36 hours). Removing mucilage bychemical could be reduced processing time. The aim of this research was to obtain the wetprocess method which easy, safe and applicable on smallholder coffee. This research had 4(four) treatments of coffee bean wet process, they were soaking in 1% sodium bicarbonatessolution for 1.5 hours, soaking in 0.3% lime solution for 0.5 hour, without fermentationand natural fermentation. The parameters observed were lightness of dry parchment coffeeand coffee bean, moisture and ash content of coffee bean, cup pH, cup quality. The best ofwet coffee processing yielded by natural fermentation and followed by soaking in 1%sodium bicarbonates solution for 1.5 hours. Nevertheless the preference score and the mostof cup quality score yielded by soaking in 1% sodium bicarbonates solution for 1.5 hoursbetter than natural fermentation. Soaking in 1% sodium bicarbonates solution for 1.5 hoursas wet process method which easy, safe and applicable on smallholder coffee.